2012
DOI: 10.1016/j.ecolmodel.2012.08.011
|View full text |Cite
|
Sign up to set email alerts
|

Implementing storm damage in a dynamic vegetation model for regional applications in Sweden

Abstract: Wind is the dominant agent of damage in forests in Western Europe. Traditional winddamage models calculate a probability for damage or a critical wind speed at which damage occurs. However, in a dynamic vegetation model actual damage to stands and individual trees is needed to get a dynamical progression of the vegetation. We present a prototype for a new approach to modelling forest wind damage at the regional scale, which we incorporate within a dynamic vegetation model. The approach is based on knowledge fr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
20
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 34 publications
(21 citation statements)
references
References 45 publications
1
20
0
Order By: Relevance
“…In Lagergren et al (2012), species-specific storm sensitivity ranked the three tree species in line with results from tree puling experiments (Peltola et al 2000), i.e. P. abies (1.0) < P. sylvestris (0.5) < deciduous species (0.1).…”
Section: Other Disturbances (Wind Damage Pest Calamities Herbivory)supporting
confidence: 52%
“…In Lagergren et al (2012), species-specific storm sensitivity ranked the three tree species in line with results from tree puling experiments (Peltola et al 2000), i.e. P. abies (1.0) < P. sylvestris (0.5) < deciduous species (0.1).…”
Section: Other Disturbances (Wind Damage Pest Calamities Herbivory)supporting
confidence: 52%
“…Recent work by Albrecht et al (2013) found no difference in the vulnerability of Douglas-fir and Norway spruce even though earlier work had suggested Douglas-fir was probably less vulnerable (Schmidt et al, 2010). Recent review studies have concluded that the most consistent factors to predisposing forest stands to wind damage are tree height, recent thinnings (approximately within the previous 5 years; Lagergren et al, 2012;Valinger and Fridman, 2011) and saturated soils (Colin et al, 2009;Hanewinkel et al, 2013).…”
Section: Logistic Regression Modelsmentioning
confidence: 91%
“…3). Adaptation and mitigation strategies are well described, especially in regard to forest management (Heinonen et al 2009;Schelhaas et al 2010;Lagergren et al 2012;O'Hara and Ramage 2013;Subramanian et al 2015). However, the sum of individual strategies does not guarantee the effectiveness of the global strategy, and systemic mitigation measures should be taken as complementary to them.…”
Section: Risk Mitigation At the Systemic Levelmentioning
confidence: 99%